Sonographic presentation acute hematometra and massive hematocolpos in a pubertal girl: A case report - Afodun, Adam Moyosore; Ukwenya, Victor Okoliko; Quadri, Khadijah Kofoworola; Malinga, Raymond Joseph; Ahimbisibwe, Octovius; Wandabwa, Julius (Journal of Biomedical Sciences, 2020)
Background: Imperforate hymen is an uncommon obstructive congenital anomaly of the female external reproductive channel due to lack of canalization (lower) vaginal plate between the vaginal and urogenital sinus; with a prevalence rate of less < 0.1%. Hematocolpos / imperforate hymen with heamatometra often presents as a pelvic mass that compresses the urinary bladder causing acute urine retention and pain. Case presentation: A 14-year-old presented with lower abdominal pain for 5 months. Patient physical examination revealed normal secondary sexual characteristics with a thickened than normal hymen. She presented with delayed menarche; a physician earlier prescribed analgesic and anthelmintic medication for pain management. After conservative hymenotomy about 360ml of dark-tan haem (blood) was drained in few minutes. Postoperative recovery was uneventful; normal menstruation occurred after 4 weeks. Conclusion: Diagnosis through physical examination and ultrasound requires vigilance and a high degree of suspicion; virginity sparing is a viable treatment option due to social reasons and religious beliefs.